Role of cardio-ankle vascular index as a predictor of left ventricular hypertrophy in the evaluation of pediatric hypertension - Evan Harvey; Noel Delos Santos; Bruce Alpert; Naema Zarish; Brittany Hedge; Ronak Naik; Ranjit Philip (Exploration of Cardiology)
Aim: Cardio-ankle vascular index (CAVI) is a marker of arterial stiffness independent of blood pressure (BP) at the time of measurement. This work sought to evaluate the association of CAVI with left ventricular hypertrophy (LVH), a marker of long-standing hypertension (HTN) in the pediatric population. Methods: CAVI values from 236 children being evaluated for HTN were compared with their BP grade (normal, elevated, stage I HTN, and stage II HTN) in accordance with clinical guidelines. CAVI values were correlated to the presence of LVH and lipid profiles. One hundred seven of the studied patients had transthoracic echocardiograms available for comparison, and 126 had available lipid results. CAVI means between the groups were compared using analysis of variance. Results: There was no significant difference in CAVI values between the BP groups [median/interquartile range: normal BP (4.95/4.4–5.7), elevated BP (5.1/4.5–5.6), stage I/II HTN (5.0/4.3–5.5)]. Mean CAVI value was higher in the group that had LVH (5.53, standard deviation = 1.4 vs. 5.1, standard deviation = 1; P = 0.13) but was not statistically significant. However, higher mean CAVI value in children ≥ 15 years was significantly associated with the presence of LVH (5.9, standard deviation = 1.8 vs. 5.2 standard deviation = 0.8; P = 0.018). Conclusions: In post-pubertal children, CAVI may be a good predictor of LVH from long-standing HTN. This tool could prove useful in screening for the presence of atherosclerotic changes and provide opportunity for intervention/improved long-term outcomes.